The interaction between obesity and sex alters the response to house dust mite in an experimental model of allergic lung inflammation - Santos-Cavalcante, Amanda; Alvarado, Alembert Lino; Capetini, Vinicius Cooper; Ricci, Julia Camargo; Anhê, Gabriel Forato; Page, Clive Peter; Riffo-Vasquez, Yanira (Frontiers in Pharmacology, 2025)
IntroductionPrevious reports have shown that the prevalence of asthma among women is modified by puberty, implying a role for sex hormones in this difference. Additionally, it has been demonstrated that obesity is a significant predisposing factor for asthma, particularly among women. In this regard, populational studies have suggested that severe asthma is more prevalent among obese patients, with worse symptoms, frequent exacerbations and hospitalisations among these patients. This study aimed to elucidate how sex and obesity interact in a murine model of lung allergic inflammation induced by house dust mite (HDM) in male and female animals.MethodsMale and female C57Bl/6 mice were maintained on a 60% high-fat diet (HFD) or a standard chow diet (SC) for 13 weeks, and on week 11, they underwent an experimental allergic lung inflammation protocol induced by HDM.ResultsOur data showed that, compared to SC-fed male mice, SC-fed female mice exhibit a more severe inflammatory response to HDM exposure. Conversely, the same difference was not observed between HFD female and male mice, with female HFD/HDM mice showing reduced infiltration of leukocytes into the lungs compared to SC/HDM female mice. Similarly, HFD/HDM mice produce lower levels of IgE, IL-5, and IL-13 in the lungs after HDM challenge. However, HFD/Sham female mice displayed notable collagen accumulation in the airways, higher concentrations of SP-D in BAL, and a decrease in the relative gene expression of PECAM-1 in their lungs prior to HDM sensitisation.ConclusionOur findings indicate that obesity and sex interact to affect allergic asthma progression in female mice by inducing a pro-inflammatory state in the lung of Sham mice, potentially altering their response to HDM.